Culture, society and sexuality: a reader - Parker, Richard G.; Aggleton, Peter (Social aspects of AIDS, 1999)
Since the beginnings of time, people have been interested in sex - the form it takes, the pleasure it can give, the circumstances in which it occurs, and what it means - both for the individuals concerned and to society more generally. Often seen as a synonym for love, sometimes as an expression of power, and infrequently as a means of exploitation and abuse, sex is a complex and multi-faceted aspect of human behaviour that has been written about by numerous writers and theorists worldwide. This book offers an introduction to the central debates in sexuality research. Among the issues examined are the social and cultural dimensions of sex, human sexuality and sex research. It will be of use to students of sociology, cultural studies, and health and behavioural studies.
Keywords: LGBTQIA2+; VIH; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques

Routledge handbook of sexuality, health and rights - Aggleton, Peter; Parker, Richard Guy (Routledge, 2010)
This handbook surveys the state of the discipline, including examination and discussion of emerging, controversial and cutting edge areas. It is an essential reference for all academics and researchers in the fields of sexuality studies, sexual health and human rights, as well as very useful reading for more advanced students.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; droits; outils; ouvrages de références; périodes historiques; santé; santé reproductive; sexualité; thématiques